Penggunaan Buku Al’arabiyyah Li Mahaarati Al-Kitaabah Fii Dhau’i . Annadzriyyati Albinaaiyyah Dalam Pembelajaran Maharah Al-Kitabah: Perspektif Media Pembelajaran - Sahkholid Nasution; Sekar Wulandari; Maulida Rahmi; Isnaini Anggina Lubis; Lisa Rahmadhani Siregar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Learning media is one of the important roles that learning brings to the successful achievement of educational goals. Books are the most basic media of the learning process as visual media. The purpose of this study is to determine the effect of the book Al'Arabiyyah Limahaarati Alkitaabah Fii Dhau'I Annadzriyyat Albinaaiyyah as a learning medium on maharah al-kitabah of Arabic Language Education-2 students in the 2021 batch of North Sumatra State Islamic University. This research is qualitative with a field research approach as well as a literature study. The results of the study show that the at-tadriibaat or the exercises themselves have a connection between the nahwu sharaf material and the maharah al-kitabah. Where, students are given the habit of writing ideas or sentences in Arabic through writing amtsilah or examples, at-tadribat or exercises, and insya' or composing assignments given every week.